2010
DOI: 10.1016/j.str.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

XLF Regulates Filament Architecture of the XRCC4·Ligase IV Complex

Abstract: SUMMARY DNA ligase IV (LigIV) is critical for non-homologous end-joining (NHEJ), the major DNA double-strand break (DSB) repair pathway in human cells, and LigIV activity is regulated by XRCC4 and XLF (XRCC4-like factor) interactions. Here, we employ X-ray scattering (SAXS) data to characterize three-dimensional arrangements in solution for full-length XRCC4, XRCC4 in complex with LigIV tandem BRCT domains and XLF, plus the XRCC4·XLF·BRCT2 complex. XRCC4 forms tetramers mediated through a head-to-head interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
147
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(161 citation statements)
references
References 47 publications
14
147
0
Order By: Relevance
“…This property arises from the distal positions of the interaction sites on both protein head domains and from the homodimeric nature of both X4 and Cernunnos. This observation agrees with low-resolution models obtained by SAXS using X4 1-140 and Cernunnos 1-248 constructs (30). In this study, the authors obtained the best fit to their experimental data by mixing tetramer, hexamer, and octamer assemblies of X4-Cernunnos.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This property arises from the distal positions of the interaction sites on both protein head domains and from the homodimeric nature of both X4 and Cernunnos. This observation agrees with low-resolution models obtained by SAXS using X4 1-140 and Cernunnos 1-248 constructs (30). In this study, the authors obtained the best fit to their experimental data by mixing tetramer, hexamer, and octamer assemblies of X4-Cernunnos.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, single mutations at any of three Cernunnos residues (R64, L65, and L115) disrupt its interaction with X4 and abrogate Cernunnos function in several DNA repair assays, despite correct Cernunnos expression and localization (29). Low-resolution models of an X4-Cernunnos complex obtained by small angle X-ray scattering (SAXS) were recently reported (30). The results of these experiments supported a head-to-head interaction model between X4 and Cernunnos and predicted a mixture of oligomers, from tetramers to octamers.…”
mentioning
confidence: 99%
“…have shown that XLF and XRCC4 form extended filaments (26,27,(38)(39)(40)(41)(42). Importantly, our SR imaging revealed that XRCC4 and XLF filaments exist in vivo, and also that LigIV appears to form filamentous structures in cells (Fig.…”
Section: Sr Imagingsupporting
confidence: 52%
“…Moreover, the involvement of LigIV with these structures was uncertain (26). Our discovery that filaments do indeed form in cells, and that these localize to DSB sites, sheds new light on the physical organization of the NHEJ repair complex (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation